Values of clear parameters for coke removal with specified powers - Kashirnaya , N.O.; Korenev , O.V.; Sorokin , E.L.; Starovoit , A.G.; Maliy , E.I.; Starovoit , M.A. (Theory and Practice of Metallurgy, 2024)
Carry out research into the optimization of the coal charge warehouse in order to replace the thick fraction of weakly adhesive coal to remove the necessary power from metallurgical coke. The investigation was carried out on the basis of the central compositional orthogonal plan. The investigation of the authorities was based on the additional significance of the structural value, abrasive hardness and flammability of the stripped coke from the added concentrate of weakly adhesive coal. With the help of a central compositional orthogonal plan, a statistical model was derived. Almost all of the different terms of the equations turned out to be significant, and some of the diversified values using the Student’s t-test showed values higher than the tabulated ones. Thus, if the equal regression is considered adequate, the remainder of the divergent values of the Fisher criterion may be more significant than the tabulated value of the Fisher criterion. The investigation made it possible to establish the patterns of influx of weakly adhesive coal concentrate into the house on the clear indications of the excess coke extracted from the mixture. Obtain the results of the investigation by infusing a concentrate of weakly abrasive coal, in addition to the central compositional orthogonal plan to allow the coking base to be expanded and the sobivartity of the coke to be reduced to be reduced.